Photocatalytic Activity of V0.13Mo0.87O2.935 Mixed Oxide for Acid Black 1 Degradation - Beyribey, Berceste; Saygi, Berrin; Corbacioglu, Burcu; Altin, Zehra; Sarac, Hanifi; Tekin, Taner (CHEM SOC PAKISTAN, 2016)
The photocatalytic activity of vanadium molybdenum oxide with a chemical formula of V0.13Mo0.87O2.935 has been studied for the first time in the literature. The effects of temperature, dye concentration of Acid Black 1, reaction time, UV light intensity and pre-treatment methods on the photocatalytic activity of V0.13Mo0.87O2.935 are presented. The highest degradation efficiency of 94% in the reaction time of 195 minutes is observed with the untreated catalyst, at 35 degrees C reaction temperature and under 88 W/m(2) light intensity for the 30 ppm initial dye concentration. The calcination and ultrasonication processes cause a decrease in the photocatalytic activity of V0.13Mo0.87O2.935 and this negative effect is attributed to the changes in the crystalline structure through these processes.
Keywords: Photocatalytic activity; Degradation; Catalysis; Acid Black 1; Vanadium molybdenum oxide; LIGHT; IRRADIATION; OXIDATION; MOLYBDATE; HYDROGEN; DYES; MOO3; Chemistry